Cloud technologies in teaching computer science of future economists - O. M. Yatsko (Academy of Cognitive and Natural Sciences, 2014)
Research goals: to analyze the main features use cloud technology in the training of computer science specialists economy and future develop recommendations for their use in the educational process of the university. Research objectives: to learn and generalize best educational experience to implement the learning process of cloud technologies and consider their strengths and weaknesses in the educational use. Object of research - the process of applying cloud technologies in teaching computer science future economists. Subject of research - cloud technology in computer science education of future economists. In order to solve the tasks used the following research methods: theory-analysis, research and systematization of literature on the study, analysis of existing government programs, empirical-diagnostic (direct and indirect observations, interviews with teachers and students, an analysis of experience of teachers) - used to determine and verify the effectiveness of methods of teaching science future professionals in the field of economics. In the results of research analyzed cloud services Google Apps for Education, Microsoft Office 365, web-oriented of computer mathematics system Sage and MathCAD Calculation Server, e-learning system Moodle, Advantages and disadvantages specified of resources, and recommendations regarding their use in teaching computer science future economists. The main conclusions and recommendations. One of the real ways to improve the training of future specialists in economics, enhance teaching and learning and research activities of students, opening their creativity, increase the role of independent and individual work is the development and implementation of the learning process of university innovative educational technologies, based on a organic combination of traditional and computer-oriented forms, methods and means of education, including the cloud.